A Functional Genomic Screen for Evolutionarily Conserved Genes Required for Lifespan and Immunity in Germline-Deficient C. elegans - Sinha, Amit (Public Library of Science, 2014)

(untitled)
The reproductive system regulates lifespan in insects, nematodes and vertebrates. In Caenorhabditis elegans removal of germline increases lifespan by 60% which is dependent upon insulin signaling, nuclear hormone signaling, autophagy and fat metabolism and their microRNA-regulators. Germline-deficient C. elegans are also more resistant to various bacterial pathogens but the underlying molecular mechanisms are largely unknown. Firstly, we demonstrate that previously identified genes that regulate the extended lifespan of germline-deficient C. elegans (daf-2, daf-16, daf-12, tcer-1, mir-7.1 and nhr-80) are also essential for resistance to the pathogenic bacterium Xenorhabdus nematophila. We then use a novel unbiased approach combining laser cell ablation, whole genome microarrays, RNAi screening and exposure to X. nematophila to generate a comprehensive genome-wide catalog of genes potentially required for increased lifespan and innate immunity in germline-deficient C. elegans. We find 3,440 genes to be upregulated in C. elegans germline-deficient animals in a gonad dependent manner, which are significantly enriched for genes involved in insulin signaling, fatty acid desaturation, translation elongation and proteasome complex function. Using RNAi against a subset of 150 candidate genes selected from the microarray results, we show that the upregulated genes such as transcription factor DAF-16/FOXO, the PTEN homolog lipid phosphatase DAF-18 and several components of the proteasome complex (rpn-6.1, rpn-7, rpn-9, rpn-10, rpt-6, pbs-3 and pbs-6) are essential for both lifespan and immunity of germline deficient animals. We also identify a novel role for genes including par-5 and T12G3.6 in both lifespan-extension and increased survival on X. nematophila. From an evolutionary perspective, most of the genes differentially expressed in germline deficient C. elegans also show a conserved expression pattern in germline deficient Pristionchus pacificus, a nematode species that diverged from C. elegans 250-400 MYA.